Mathematics Learning in the 21st Century: Problem-Based Learning (PBL) and GenAI - Eko Fajar Suryaningrat; Ejen Jenal Mutaqin; Karantiano S Putra; Arini Fitria Nurfadilah; Nazma Rahma Aullia (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Mathematics education in the 21st century faces the challenge of developing students' critical and creative skills in addressing complex problems. One increasingly popular approach is Problem-Based Learning (PBL), which focuses on providing real-world problems for students to solve collaboratively. PBL not only introduces students to mathematical concepts but also develops their problem-solving skills, critical thinking, and collaboration. On the other hand, technological advancements, particularly in Generative Artificial Intelligence (GenAI), open new opportunities to support mathematics learning. With its ability to automatically generate content, GenAI can be used to present more dynamic and interactive learning materials, as well as help students explore mathematical concepts in greater depth. This study aims to explore the integration of PBL with GenAI in the context of mathematics education in the 21st century. It is expected that this combination will not only enhance the understanding of mathematical concepts but also prepare students to adapt to the rapid development of technology. This research will discuss the benefits, challenges, and implications of applying these two approaches to improve the effectiveness of mathematics education in schools and universities.Pendidikan matematika abad ke-21 menghadapi tantangan dalam mengembangkan keterampilan kritis dan kreatif siswa untuk menyelesaikan masalah kompleks. Problem-Based Learning (PBL) menjadi pendekatan populer, karena mengajarkan pemecahan masalah, berpikir kritis, dan kolaborasi melalui masalah dunia nyata. Di sisi lain, kemajuan Generative Artificial Intelligence (GenAI) menawarkan peluang baru dalam mendukung pembelajaran matematika dengan menghasilkan konten secara otomatis, memungkinkan siswa mengeksplorasi konsep matematika secara lebih interaktif. Penelitian ini bertujuan mengeksplorasi integrasi PBL dan GenAI dalam pendidikan matematika. Metode yang digunakan adalah studi literatur untuk menganalisis penerapan kedua pendekatan ini. Hasil menunjukkan bahwa kombinasi PBL dan GenAI dapat meningkatkan pemahaman matematika siswa dan mempersiapkan mereka menghadapi perkembangan teknologi. Namun, tantangan muncul dalam kesiapan teknologi, keterampilan guru, dan infrastruktur yang memadai. Simpulan dari penelitian ini adalah bahwa integrasi PBL dan GenAI berpotensi meningkatkan efektivitas pembelajaran matematika, tetapi memerlukan pelatihan bagi guru dan pengembangan infrastruktur untuk memaksimalkan manfaatnya di sekolah dan perguruan tinggi.